Bridging the Gap: Exploring Religious Literacy as an Alternative Approach to Religious Education in Indonesia - Imamah, Fardan Mahmudatul; Lee, Hongsok (Analisa: Journal of Social Science and Religion, 2024)
This research addresses the problem of religious education in Indonesia, which often focuses solely on theological education and causes alienation among religious communities. The study aims to explore religious literacy as an alternative to bridge this gap. This qualitative research uses Critical Discourse Analysis (CDA) by Norman Fairclough, analyzing one transcript based on a video lecture in an academic setting, four videos on international seminars, one short school video, and two talk shows on “Religious Literacy Indonesia” on YouTube. The analysis examines how religious literacy is described in the current religious education discourse, identifies the scholars involved, and explores the implications of religious literacy on the discourse of religious education. The result shows that religious literacy in Indonesia has adapted to government policies and educational needs, focusing on practical skills for religious teachers and extension officers. It collaborates with the government for effectiveness but remains mostly within academic circles, with limited public understanding. Challenges include maintaining religious identity and boundaries in interfaith learning. Religious literacy is expected to build social trust, which requires creating shared moral spaces among different religions and aiming for positive outcomes in interfaith relations.